Analisis Wsm Dan Wp Dalam Menentukan Pupuk Terbaik Dengan Pendekatan Wsm-Score Dan Vector - Asyahri Hadi Nasyuha; Suardi Yakub; Widiarti Rista Maya; Yohanni Syahra; Saniman Saniman (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2021)
Fertilizer is a material that is given to the soil or plants to meet the nutritional needs of the plant. Fertilization needs to be done rationally according to plant needs. In the supply of fertilizer, farmers have difficulty in determining the best fertilizer for their crops, making it difficult to choose which fertilizers are good for their crops. In determining the best fertilizer, a decision support system can be used as an alternative to help someone make decisions more effectively and efficiently by utilizing certain data and models. To solve the existing problems, it is necessary to conduct research in decision making using the Weighted Sum Model (WSM) and Weight Product (WP) Methods which can produce decisions based on the best fertilizer criteria that will be purchased by customers. The Weighted Sum Model (WSM) method is one of the simplest and easiest methods to understand its application, this method is also part of the MCDM (Multi-Criteria Decision Making) method in evaluating the value of each alternative. The Weight Product (WP) method is a method using multiplication to relate the attribute rating, where the rating of each attribute must be ranked with the attribute weight in question. From the results of the implementation of this system, it can be concluded that using the Weighted Sum Model and Weight Product method can help customers in the decision-making process for choosing the best fertilizer to use on their plants.